Trade Potential Of India With Mercosur Countries Using Revealed Comparitive Index Method - Verma, Ms Sabina; Dhami, Dr Jasdeep Kaur (The journal of contemporary issues in business and government, 2021)
Founded in 1991, by signing a treaty of Asuncion among four founder member countries comprising of Argentina, Brazil, Uruguay and Paraguay is an intergovernmental association and was a beginner step to create free trade area. It’s been three decades from the establishment, the demise of southern cone common market has been announced several times; may it be Brazilian Devaluation(1999), Argentina Economic Crisis(2001- 02), Global Economic Crisis(2008) but still MERCOSUR has survived, deliver democratic stability, increased trade flows and international exposure to its member countries. In this research paper we will analyse the India’s trade potential with Mercosur countries for different product lines. This article will firstly review the historical evolution of MERCOSUR, then will discuss the trade potential of Mercosur nations and India and finally explores the challenges that are being faced.